Sources of the aeolian material in periglacial conditions based on quartz grain analysis, Ebba Valley, Svalbard - Rymer, Krzysztof Grzegorz; Wachecka-Kotkowska, Lucyna (Quaestiones Geographicae, 2024)
The research conducted in this study is an attempt to quantitatively and qualitatively supplement the still insufficient knowledge on aeolian processes under polar conditions, where some of the most visible and dynamic climate changes are occurring. This study presents the results of rounding and matting analysis of quartz grains collected from aeolian deposition traps located in the Ebba Valley, Svalbard. The results are based on four summer field campaigns (2015–2018). Quartz grains with a diameter of 0.8–1.0 mm were selected and subjected to further analysis under a microscope, which allowed them to be divided into six individual classes. The nature of the grains can largely indicate the environmental conditions in which the material was transported. The collected material was dominated by grains with a low degree of roundness, which may indicate relatively short fluvial or aeolian transport. The small amounts of typically matted quartz grains may indicate low environmental dynamics and short transport, as well as the fact that large amounts of the material are blown from the valley interior to the nearby bay and fjord. This study highlights the importance of a fresh sediment supply from two main sources (i.e., moraines and rivers) and their subsequent aeolian redistribution, particularly in a wind-channelled valley environment. These findings underscore the complex interactions between aeolian processes and environmental conditions in cold regions. Climate change may significantly affect the magnitude of aeolian processes. Further research is needed to refine these correlations and enhance the understanding of sedimentary dynamics in polar settings.